Respuesta :

[tex]\bf \textit{let's recall that }sin^2(\theta)+cos^2(\theta)=1 \\\\\\ sin^2(\theta)=1-cos^2(\theta)\implies sin(\theta )=\sqrt{1-cos^2(\theta)}\\\\ -------------------------------\\\\[/tex]

[tex]\bf y=sin(x)cos(x)\impliedby \textit{now, using the product-rule} \\\\\\ \cfrac{dy}{dx}=cos(x)cos(x)-sin(x)cos(x)\implies 0=cos(x)[cos(x)-sin(x)]\\\\ -------------------------------\\\\ 0=cos(x)\implies \boxed{\measuredangle x= \begin{cases} \frac{\pi }{2}\\\\ \frac{3\pi }{2} \end{cases}}\\\\ -------------------------------\\\\[/tex]

[tex]\bf 0=cos(x)-sin(x)\implies sin(x)=cos(x)\\\\ thus\qquad \sqrt{1-cos^2(x)}=cos(x)\implies 1-cos^2(x)=cos^2(x) \\\\\\ 1=2cos^2(x)\implies \cfrac{1}{2}=cos^2(x)\implies \pm\sqrt{\cfrac{1}{2}}=cos(x) \\\\\\ \pm\cfrac{1}{\sqrt{2}}=cos(x)\implies \pm\cfrac{\sqrt{2}}{2}=cos(x)\implies \boxed{\measuredangle x= \begin{cases} \frac{\pi }{4}\\\\ \frac{3\pi }{4}\\\\ \frac{5\pi }{4}\\\\ \frac{7\pi }{4} \end{cases}}[/tex]